The Effect of Madrasah Principal's Leadership and Teachers' Work Motivation on Learning Effectiveness in Bandar Lampung - Abas, Erjati (SCAD Independent, 2019)
This study aims to determine and analyze the effect of principal's leadership and teachers’ work motivation on the effectiveness of learning in MTsN Bandar Lampung. The method used is a type of quantitative research that aims to test hypotheses using statistical techniques. The most basic data collection method is a questionnaire (questionnaire). The sample in this study is teachers at MTsN Bandar Lampung. Moreover, the data analysis techniques using simple correlation statistical tests and multiple linear regressions, the results of the study show: 1). There is the effect of the headmaster's leadership with the effectiveness of learning in MTsN Bandar Lampung with the effect power of 0.923 which is categorized as very strong; 2). There is a significant effect between teachers’ work motivation and learning effectiveness in MTsN Bandar Lampung with the effect strength of 0.949 which is categorized as very strong; 3). There is the effect of the headmaster's leadership and teachers’ work motivation together with the effectiveness of learning in MTsN Bandar Lampung because the value of r is smaller than the level used (ie 0.05) or 0,000 <0.05.